Asymmetric Dimethylarginine (ADMA) Levels Display a Morning Peak in Patients with Acute Myocardial Infarction. Issue 5 (28th May 2013) - Bergheanu, Sandrin C.; van der Laarse, Arnoud; van der Bom, Johanna G.; van der Hoeven, Bas L.; le Cessie, Saskia; de Jong, Margreet G.; Liem, Su-San; Schalij, Martin J.; Jukema, J. Wouter
Abstract : High Asymmetric Dimethylarginine (ADMA) levels are associated with increased platelet activity, elevated blood pressure, vasoconstriction and impaired vascular relaxation. We hypothesized that the myocardial infarction morning peak of occurrence is closely related to a morning peak of ADMA levels. We performed a cross-sectional study among patients with documented myocardial infarction who had been enrolled in the prospective MISSION! Intervention Study. In total, serum ADMA levels were measured in their acute setting of myocardial infarction in 120 patients. The frequency of myocardial infarction onset of symptoms and emergency coronary catheterization and the ADMA levels displayed a similar daily pattern with a morning peak between 06:00–11:59 h. The absolute ADMA levels peak was between 06:00–07:59 h with a median (interquartile range) peak value of 1.01 (0.84–1.21) μmol/L for the n = 9 patients vs. 0.75 (0.61–0.89) μmol/L for the remaining 111 patients admitted throughout the rest of the 24-hour interval ( p = 0.003 for between groups comparison). The amplitude (95% confidence interval) of the circadian variation of ADMA levels was 0.08 μmol/L (0.004–0.16) with p = 0.042 for statistic model significance. In conclusion, ADMA levels display a 24-hour variation with a significant morning peak in patients with acute myocardial infarction. These findings may relate ADMA levels to the acute onset of thrombotic cardiovascular events.